Planting Density Affects Panax notoginseng Growth and Ginsenoside Accumulation by Balancing Primary and Secondary Metabolism - Liu, Haijiao; Gu, Hongrui; Ye, Chen; Guo, Cunwu; Zhu, Yifan; Huang, Huichuan; Liu, Yixiang; He, Xiahong; Yang, Min; Zhu, Shusheng (Frontiers in Plant Science, 2021)
Adjusting planting density is a common agricultural practice used to achieve maximum yields. However, whether the yield and quality of medicinal herbs can be simultaneously improved by implementing appropriate planting densities is still uncertain. The medicinal crop Panax notoginseng was used to analyze the effects of planting density on growth and ginsenoside accumulation, and the possible mechanisms of these effects were revealed through metabonomics. The results showed that P. notoginseng achieved higher dry biomass and ginsenoside accumulation at a moderate planting density (15×15 cm) than at lower (20×20 cm and 30×30 cm) or higher planting densities (8×8 cm and 10×10 cm). At the moderate planting density, the primary metabolism (starch and sucrose metabolism) and secondary metabolism (the biosynthesis of phytohormone IAA and ginsenoside) of the plants were significantly enhanced. However, the strong intraspecific competition at the higher planting densities resulted in stress as well as the accumulation of phytohormones (SA and JA), antioxidants (gentiobiose, oxalic acid, dehydroascorbic acid) and other stress resistance-related metabolites. Interestingly, the dry biomass and ginsenoside content were significantly lower at low densities with low intraspecific competition, which disturbed normal carbohydrate metabolism by upregulating galactose metabolism. In summary, an appropriate planting density was benefit for the growth and accumulation of ginsenosides in P. notoginseng by balancing primary metabolism and secondary metabolism.